Role of P2 X7 receptor during focused ultrasound induced blood brain barrier modulation - Junwon Park; Young Cheol Na; Jihyeon Lee; Younghee Seo; Hojin Kim; Sangheon Han; Byeong-Wook Song; Won Seok Chang (Scientific Reports)
Abstract Although low-intensity focused ultrasound (LiFUS) with microbubbles is used to temporally open the blood-brain barrier (BBB), the underlying mechanism is not fully understood. This study aimed to analyze BBB-related alterations in the brain microenvironment after LiFUS, with a focus on the involvement of the purinergic P2 X7 receptor. Sprague-Dawley rats were sonicated with LiFUS at 0.3 MPa energy. The impact of LiFUS on the P2 X7 receptor and inflammatory-related proteins, including NLRP3 and interleukin-1β, was analyzed through western blotting. The BBB-associated tight junction proteins, zonula occludens-1 (ZO-1) and occludin, were also analyzed. BBB permeability was assessed by quantifying the amount of Evans blue dye penetration using spectrophotometry. Furthermore, the safety of the sonication procedure was verified via terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay and hematoxylin and eosin staining. Substantial increases in the P2 X7 receptor and its downstream signaling were confirmed after sonicating the BBB with LiFUS for 1 h (p < 0.05). Conversely, for tight junction proteins, the lowest expression was observed at 1 h (p < 0.001). Both responses were normalized back to the original state over time. No evidence of brain damage was observed during the procedure. Furthermore, the P2 X7 receptor antagonist-injected group showed reduced Evans blue dye penetration compared to that 1 h after FUS, indicating a mitigated impact of LiFUS on the BBB. Herein, we elucidate the underlying mechanism by which LiFUS affects the BBB, with a focus on the involvement of the P2 X7 receptor. Our findings demonstrate that the extent of BBB opening varies upon the regulation of the P2 X7 receptor. This study provides valuable insights into the mechanisms underlying BBB modulation through LiFUS, thereby laying the foundation for expanding its applications.